Chemical characterization of pineapple leaf residue chars generated by controlled combustion and by open burning - Lee, Yit Leng; Mohd Hanif, Ahmad Husni; Abd. Wahid, Samsuri; Abdul Razak, Norawanis; Makhtar, Nur Lailina; Ismail, Ras Izzati (EDP Sciences, 2016)
This study was undertaken to compare the chemical characteristics of pineapple leave residues (PLRs) char generated by controlled combustion and by open burning. The properties of char generated by control combustion (CC) and open burning (OB) varied, due to differences in the production process. The total N, K and surface area of the char generated by CC were significantly higher than the OB. The results indicate that the CC process was better to be applied as a soil amendment than was the OB process.